Giardia duodenalis enolase is secreted as monomer during trophozoite-epithelial cell interactions, activates plasminogen and induces necroptotic damage - Barroeta-Echegaray, Elisa; Fonseca-Liñán, Rocío; Argüello-García, Raúl; Rodríguez-Muñoz, Rafael; Bermúdez-Cruz, Rosa María; Nava, Porfirio; Ortega-Pierres, M. Guadalupe (Frontiers in Cellular and Infection Microbiology, 2022)
Enolase, a multifunctional protein expressed by multiple pathogens activates plasminogen to promote proteolysis on components of the extracellular matrix, an important event in early host-pathogen interactions. A secreted form of enolase that is released upon the interaction of trophozoites with epithelial cells has been detected in the secretome of G. duodenalis. However, the role of enolase in the host-pathogen interactions remains largely unknown. In this work, the effects of G. duodenalis enolase (Gd-eno) on the epithelial cell model (IEC-6) were analyzed. Firstly, the coding sequence of Giardia enolase was cloned and the recombinant protein used to raise antibodies that were then used to define the localization and role of enolase in epithelial cell-trophozoite interactions. Gd-eno was detected in small cytoplasmic vesicles as well as at the surface and is enriched in the region of the ventral disk of Giardia trophozoites. Moreover, the blocking of the soluble monomeric form of the enzyme, which is secreted upon interaction with IEC-6 cells by the anti-rGd-eno antibodies, significantly inhibited trophozoite attachment to intestinal IEC-6 cell monolayers. Further, rGd-eno was able to bind human plasminogen (HsPlg) and enhanced plasmin activity in vitro when the trophozoites were incubated with the intrinsic plasminogen activators of epithelial cells. In IEC-6 cells, rGd-eno treatment induced a profuse cell damage characterized by copious vacuolization, intercellular separation and detachment from the substrate; this effect was inhibited by either anti-Gd-eno Abs or the plasmin inhibitor ϵ- aminocaproic acid. Lastly, we established that in epithelial cells rGd-eno treatment induced a necroptotic-like process mediated by tumor necrosis factor α (TNF-α) and the apoptosis inducing factor (AIF), but independent of caspase-3. All together, these results suggest that Giardia enolase is a secreted moonlighting protein that stimulates a necroptotic-like process in IEC-6 epithelial cells via plasminogen activation along to TNFα and AIF activities and must be considered as a virulence factor.